2019
DOI: 10.1093/femsle/fnz153
|View full text |Cite
|
Sign up to set email alerts
|

Dietary butyrate suppresses inflammation through modulating gut microbiota in high-fat diet-fed mice

Abstract: Butyrate, a key metabolite fermented by gut microbiota mainly from undigested carbohydrates such as dietary fibers is widely used as feed additive. However, mechanisms of its contributions in maintaining host health are relatively poorly revealed. The aim of this study was to investigate how butyrate impacts gut microbiota and immunity response in high-fat diet-fed mice. Gut microbial analysis exhibited that butyrate intervention increased SCFAs-producing bacteria and decreased pathogenic bacteria, such as end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…117 This inhibitory effect of butyrate on TLR4 expression was also observed in mouse adipose tissue in vivo. 118 Sodium butyrate significantly decreased the TLR4 and NFKB signaling pathways in lipopolysaccharide-induced acute lung injury in mice. 119 In addition, butyrate inhibits the NF-kB pathway in the HT-29 colon cancer cell line.…”
Section: Butyrate Contributes To the Anti-inflammatory Effect Inducedmentioning
confidence: 94%
“…117 This inhibitory effect of butyrate on TLR4 expression was also observed in mouse adipose tissue in vivo. 118 Sodium butyrate significantly decreased the TLR4 and NFKB signaling pathways in lipopolysaccharide-induced acute lung injury in mice. 119 In addition, butyrate inhibits the NF-kB pathway in the HT-29 colon cancer cell line.…”
Section: Butyrate Contributes To the Anti-inflammatory Effect Inducedmentioning
confidence: 94%
“…Increasing attention has been paid to butyrate for its protective role against the pathophysiological processes of obesity [11]. Butyrate has been shown to have a number of different effects on the host including improvement of gut barrier function [12], suppression of the pro-inflammatory response [13,14], and secretion of gut hormones, such as glucagon-like peptide-1 [15], all of which could contribute to alleviation of obesity and related metabolic abnormalities. Butyrate has also been shown to decrease food intake and increase cholecystokinin (CCK)-induced satiety and reduce hepatic fat accumulation; there is evidence to suggest that these actions are mediated via an effect on the gut-brain neural circuit [16].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the effects of decreased microbial synthesis of butyrate in the gut (Fig. 7C), since it has previously been reported that Planctomycetaceae are more abundant in guts containing lower levels of butyrate (Zhai et al 2019). Both the P-and N-limited groups had more Streptococcaceae in their gut; indeed, previous reports indicate that the presence of Streptococcaceae in the gut is highly associated with metabolic disorders of the host (Aran et al 2011, Qiao et al 2014.…”
Section: Variations In the Intestinal Microbial Community In Nutrientmentioning
confidence: 60%